(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: To compare the anaesthetic efficacy of mental nerve block via two different techniques, i.e., to inject local anaesthesia in between the roots of two premolars and to give local anaesthesia distal to the second premolar, among patients requiring extractions of a mandibular premolar or anterior teeth bilaterally. PATIENTS AND METHODS: A prospective, randomized-controlled, split-mouth clinical study was implemented. Healthy adult patients between the ages of 12-65 years seeking extraction of the mandibular anterior and both premolar teeth were included in this study. Teeth extractions were randomly assigned to two equal groups while giving a mental nerve anaesthesia to inject local anaesthesia in between the roots of two premolars (group 1) and to give local anaesthesia distal to the second premolar (group 2). After 5 min of local anaesthetic injection, the tooth was extracted, and each patient was asked to record the intensity of the extraction pain using the Visual Analogue Scale (VAS). RESULT: 84 patients with a mean age of 12-65 years were studied. The results showed a 61.4% success rate for injections distal to the second premolar and a 56.8% success rate for injections between premolars. CONCLUSION: No significant difference was found; however, slight favoring results for the technique used distal to the premolar as compared to injecting in between the first and second premolar.